DIPLOMASI BUDAYA INDONESIA DALAM MENINGKATKAN PUBLIKASI LITERASI INDONESIA TERHADAP FRANKFURT BOOK FAIR JERMAN - Aina Khansa (2020)
Literacy culture is very important to be built in a country. The problem that arises is the aspect that can improve the literacy culture of Indonesian people, namely the publication of literacy itself that can be accessed by all Indonesian people. Not only in Indonesia. Literacy publications are also needed internationally. The government has made many programs to improve Indonesian literacy publications both nationally and internationally. In the international sphere, the government cooperates with Indonesian ambassadors to attend international exhibitions and become honored guests at the Frankfurt Book Fair. The election of Indonesia was motivated by the existence of diplomacy conducted by the Indonesian government with the Frankfurt Book Fair. Diplomacy is done because there are things that both parties want to achieve. Then use the concept of cultural diplomacy because Indonesian representatives who are dispatched are not only exhibitors who then become diplomatic actors using aspects of the culture they bring, namely literacy, culinary, music and others. From this cultural diplomacy, Indonesian literacy is able to be well publicized with the purchase of copyrights to several hundred books that have been sent for publication and publication in various languages and countries. Then Indonesia is able to build an international community branding towards Indonesia which is multicultural and has a high tolerance for others. This can be seen from what Indonesia has taken such as literacy from various themes, pavilions which are divided into several islands that reflect the diversity of Indonesian culture.